2011
DOI: 10.1016/j.jaci.2011.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and asthma: An association modified by age of asthma onset

Abstract: Background Studies of asthma phenotypes have identified obesity as a component of a group characterized by a high proportion of adult-onset asthmatics. However, whether age of asthma onset modifies the association between obesity and asthma is unknown. Methods From the Severe Asthma Project (SARP), we defined age of asthma onset as early (before 12 years of age) and late-onset (12 and higher). Comparisons of body mass index (BMI) categories were done within age of onset groups and obesity was also compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
1
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(176 citation statements)
references
References 25 publications
2
163
1
10
Order By: Relevance
“…Obesity and sleep apnoea are more likely to be associated with a neutrophilic asthma phenotype than an allergic and/or eosinophilic asthma phenotype, offering an explanation for the reduced probability of reaching an optimal asthma control level with traditional asthma therapy such as inhaled corticosteroids, long-acting bronchodilators and antileukotrienes [23,26,27]. Obesity has been associated with asthma both as a risk factor for asthma and as a modifying factor of the disease [28,29]. Since this was a questionnaire study we did not have the option of studying sputum samples to differentiate between eosinophilic and neutrophilic asthma phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and sleep apnoea are more likely to be associated with a neutrophilic asthma phenotype than an allergic and/or eosinophilic asthma phenotype, offering an explanation for the reduced probability of reaching an optimal asthma control level with traditional asthma therapy such as inhaled corticosteroids, long-acting bronchodilators and antileukotrienes [23,26,27]. Obesity has been associated with asthma both as a risk factor for asthma and as a modifying factor of the disease [28,29]. Since this was a questionnaire study we did not have the option of studying sputum samples to differentiate between eosinophilic and neutrophilic asthma phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity-related asthma is also associated with greater disease burden among those who developed asthma in their pre-adolescent years as compared to those who develop symptoms in adulthood (Holguin F et al, 2011). Pulmonary function decline in association with obesity is greater among those who develop asthma as pre-adolescent children and adolescents than those who develop it as adults (Lang JE et al, 2011).…”
Section: Childhood Asthmamentioning
confidence: 99%
“…Longitudinal studies 5,6,7 have found that development of obesity in school age years is associated with greater incident asthma during adolescence. Several groups have found that among individuals with asthma, those who are obese have worse control, greater need for albuterol and oral corticosteroids, are more often hospitalized, have a decreased response to inhaled corticosteroids, and have lower quality of life 8,9,10,11,12 . Furthermore, weight gain worsens asthma symptoms among those with severe or difficult-to-treat asthma 13 , and weight loss improves both asthma control and lung function 14,15,16 .…”
Section: Introductionmentioning
confidence: 99%